José Martí, Lucía Jerez. Ed. y pról. de Mauricio Núñez Rodríguez. Centro de Estudios Martianos, La Habana, 2000; 173 pp. - Sánchez Aguilera, Osmar (El Colegio de México, 2001)
Se reseñó el libro: Lucía Jerez. Ed. y pról. de Mauricio Núñez Rodríguez.